UPAYA MENINGKATKAN HASIL BELAJAR TENIS MEJA MELALUI MEDIA DINDING SDN 2 KAPUAS HULU TAHUN PELAJARAN 2016/2017 - Mursidi, Mursidi; Simanjuntak, Victor G; Haetami, Mimi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract:The problem in this research is how to improve the learning result of table tennis lhruugh /he wall media on the students of  clas:. V SDN 2 Ncmga Dangka11 Silat Hutu District Kapuas Hulu Regency ?. Thepurpose of this study is to determine the increase in learning outcomes ofplaying table tennis in the students class V SDN 2 Nanga Dangkan Sila1 Huitt District Kapuas Hutu regency through the application by modifying the replaced opponent with the wall. This study uses classroom action research which is the basisfor improving the learning that will be produced,  with thefollowing steps: l) Planning; 2) implementation: 3) observation; 4) reflection; Subjects in use as many as 21 sh1dents. Data were collected by questionnaire I questionnaire and test each (..yc/e. From the results of the study ln the preljminary test before the actfon  was seen  that  the  value  of learning  table  tennis  blow averaged  65.29 class and  the number  of percentage  of classical  completeness reached  only  14_29% Jn  rhe firsr  cycle  action with learning method  using wall media at learning table tennis punch obtained the average value of class 72.14 percentage  of classical completeness 61.90%. In the second cycle action with the ganze gamepakarm?jang can improve learning long jurnp style squat obtained average learning outcomes 77 with classical completeness increased by 96% and the value of student activity observation the better. In the second cycle action with learning metlwd  using wall media at leaming table  tennis punch  in cable  1ennis material obtained grade average value that is 77,62 the percentage  of classical completeness also increase until reach 90,48% and observation value of student activity is belter. Keywords: Learning outcomes, Table tennis, Media, Wall